Reinterpreting the LearnDirect Model to Achieve Successful Communities of Practice - Hramiak, Alison (Proceedings of the International Conference on Networked Learning, 2002)
For many students, the specific requirements of their cultural background can serve as a barrier to realising their learning potential. In such cases, the distance to an educational establishment may be more a cultural than geographical mile. Technology may, for some, be the only way to travel this mile, and thus enable learning to take place where once it might have not.